2014
DOI: 10.1016/j.mayocp.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Sex Differences in Fatty Liver on Cardiac Computed Tomography: The Multi-Ethnic Study of Atherosclerosis

Abstract: Objective To describe ethnic and gender differences in the prevalence and determinants of fatty liver in a multi-ethnic cohort. Patients and Methods We studied participants from the Multi-Ethnic Study of Atherosclerosis who underwent baseline non-contrast cardiac CT between July 2000-August 2002, and had adequate hepatic and splenic imaging for fatty liver determination (n=4088). Fatty liver was diagnosed by a liver/spleen attenuation ratio <1. We compared the prevalence and severity of fatty liver, among fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 52 publications
0
29
1
Order By: Relevance
“…For example, in community-based US data from the 2000 to 2002 MESA study participants, nonalcoholic fatty liver disease was present in 17% of African Americans with metabolic syndrome but was present in 39% of Hispanics with metabolic syndrome. 23 The phenotypic expression of metabolic syndrome also varies by country and culture, particularly in Europe. 24 …”
Section: Metabolic Syndromementioning
confidence: 99%
“…For example, in community-based US data from the 2000 to 2002 MESA study participants, nonalcoholic fatty liver disease was present in 17% of African Americans with metabolic syndrome but was present in 39% of Hispanics with metabolic syndrome. 23 The phenotypic expression of metabolic syndrome also varies by country and culture, particularly in Europe. 24 …”
Section: Metabolic Syndromementioning
confidence: 99%
“…Noncontrast cardiac CT images were obtained with a cardiac-gated CT scanner (Phillips 16D or Toshiba MSD Aquillion 64 at the University of California, San Francisco, and Siemens Sensation Cardiac 64 at Northwestern University) to assess pericardial fat volume and hepatic fat attenuation. Measurement methods and reading centers were similar to those used in MESA (20). …”
Section: Methodsmentioning
confidence: 99%
“…[44][45][46][47] Whether sex affects NAFLD natural history and mortality is uncertain, although studies have suggested a worse outcome in men. 45,48,49 The prevalence of NAFLD follows a gradient Hispanics >Whites-Caucasians >Afro-Americans [50][51][52][53] and ethnicity may modulate the association between NAFLD, sex and MetS features. For example, NAFLD is more common in men than in women among Whites, but not among Blacks or Hispanics.…”
Section: 15mentioning
confidence: 99%
“…In contrast, Hispanics have the highest prevalence of NAFLD, including the obese and MetS population. 53 Interestingly, among patients with NAFLD, African Americans have NASH less frequently than…”
Section: 15mentioning
confidence: 99%